Assessing the effect of sustainability initiatives of local manufacturing industries in employee motivation - Arcojada, Angeline G., Carable, Julius Hendrix F., David, Maryanne S., Egana, Jamaica Joy B., Florido, Bianca Marie C., Laurente, Alyanna D., Mendoza, Arvhin D. 4 0 16; 5
Abstract As sustainability becomes increasingly significant in organizational practices, the study seeks to explore how sustainability initiatives affect the motivational aspects of employees within the local market. The study goes beyond examining the correlation between sustainability initiatives and employee motivation. It investigates the underlying factors contributing to this relationship with demographic profile as the external variables. The researchers employed survey questionnaires on 320 employees of the Philippines' plastic manufacturing industry, Manly Plastics Inc. Collectively, the results imply that companies implementing sustainability initiatives experience increased employee eagerness and motivation, creating an environment where individuals are more inclined to perform at their best. However, the study lacks sufficient evidence to substantiate variations in motivation levels across different demographic groups. Keywords: Initiative, Sustainability, Employee Motivation
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2